Constructing the Higher Education Student Perspectives from across Europe - Brooks, Rachel (Policy Press, 2022)
EPDF available Open Access under CC-BY-NC-ND licence. Amid debates about the future of both higher education and Europeanisation, this book is the first full-length exploration of how Europe's 35 million students are understood by key social actors across different nations. The various chapters compare and contrast conceptualisations in six nations, held by policymakers, higher education staff, media and students themselves. With an emphasis on students' lived experiences, the authors provide new perspectives about how students are understood, and the extent to which European higher education is homogenising. They explore various prominent constructions of students - including as citizens, enthusiastic learners, future workers and objects of criticism.